DOI: 10.11606/d.2.2018.tde-01102020-210350
|View full text |Cite
|
Sign up to set email alerts
|

Anualidade orçamentária e contratos administrativos

Abstract: This dissertation focuses on the relation between budget annuality, as a public budget's peculiar feature, and administrative contracts. The research explores the conflict between the Public Administration's binding to these contracts, especially the multiannual ones, and the need for annual legislative authorization, as an essential element of the public budget, for the execution of public expenditures required to fulfill these contractual obligations. Is explored the notion of public budget, scanning its con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…pseudorroseus Moreno et al, 1981. However, although this genus has been accepted by some authors (Rota, 2013) others deny its existence and include it within the genus Eiseniona (Blakemore, 2008). There is also some controversy about the systematic position of two other Iberian endemic species Aporrectodea oliveirae Rosa, 1894 and Eiseniona gerardoi Díaz Cosín et al, 2014, where some molecular phylogenetic analyses have shown them to belong to Iberoscolex (Díaz Cosín et al, 2014; Domínguez et al, 2015)—and they are treated as such in this work.…”
Section: Introductionmentioning
confidence: 99%
“…pseudorroseus Moreno et al, 1981. However, although this genus has been accepted by some authors (Rota, 2013) others deny its existence and include it within the genus Eiseniona (Blakemore, 2008). There is also some controversy about the systematic position of two other Iberian endemic species Aporrectodea oliveirae Rosa, 1894 and Eiseniona gerardoi Díaz Cosín et al, 2014, where some molecular phylogenetic analyses have shown them to belong to Iberoscolex (Díaz Cosín et al, 2014; Domínguez et al, 2015)—and they are treated as such in this work.…”
Section: Introductionmentioning
confidence: 99%